The Relationship Between Pharmaceutical Service Quality And Outpatient Satisfaction: HUBUNGAN KUALITAS PELAYANAN FARMASI DENGAN KEPUASAN PASIEN RAWAT JALAN - Raya, Yuni; Retno, Yosy; Kesuma, Andini; Armein; Muhajirin, Al; Oktora, Bunga; Fitrianingsih, Nining; Yuliana; Bustomi; Fajar, Anisya (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Improving the quality of hospital services cannot be separated from the organization of pharmaceutical installations. Therefore, it is meaningful to focus on the quality of pharmacy installation services so that patient satisfaction can be obtained, which is in the form of convenience, speed, relationship, ability and hospitality addressed through attitudes and characteristics in providing services for consumer satisfaction. Objective: To analyze the relationship between pharmacy service quality and outpatient satisfaction. Methods: This research is correlational analytic with a cross sectional approach. The population in this study were 150 people, the number of samples in this study amounted to 75 patients with Non Probability Sampling technique using Accidental Sampling method. The results of the study were tested with the Kendall tau statistical test with a significance of α = <0.05 with the SPSS 25 program. The research instrument used a quality questionnaire and a patient satisfaction questionnaire. This research was conducted at RSUD Ciawi Bogor. Results: The results of the Kendall tau test with an error rate (α) = 0.05, obtained a p value = 0.484. This means that there is no significant relationship between the quality of pharmaceutical services and outpatient satisfaction. Conclusion: There is no relationship between pharmaceutical service quality and outpatient satisfaction at RSUD Ciawi, Bogor Regency.